A Contribution of Madrasah Head: Building Quality School Culture at MAN 2 Cirebon - Masruhah, Masruhah; Djubaedi, Dedy (CV Kalimasada Group, 2023)
This paper describes one of the contributions of the madrasah head at MAN 2 Cirebon as an effort to create competitive education by building a quality school culture. A qualitative approach was used, by collecting primary data sources from observations and interviews; while secondary data was obtained by digging from books, articles related to the discussion, from internet searches. The finding is that there is a new culture that is now built by the madrasah head as a form of his contribution by integrating technological innovation in learning as well as promoting institutions and student robotic extracurricular activities. The novelty of this research is the technological innovation program implemented at MAN 2 Cirebon. The limitations of this research are a review of other similar studies.